1998
DOI: 10.1056/nejm199804023381403
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Transmission and the Natural History of Human Herpesvirus 8 Infection

Abstract: The prevalence of HHV-8 infection is high among homosexual men, correlates with the number of homosexual partners, and is temporally and independently associated with Kaposi's sarcoma. These observations are further evidence that HHV-8 has an etiologic role in Kaposi's sarcoma and is sexually transmitted among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
405
2
19

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(454 citation statements)
references
References 27 publications
28
405
2
19
Order By: Relevance
“…In these countries, horizontal transmission and mother-to-child transmission are likely to occur (Bourboulia et al, 1998;Luppi et al, 1998;Gessain et al, 1999). In countries with a low incidence of classic or endemic KS, HHV-8 is predominantly found in homosexual men at risk of developing KS Martin et al, 1998;Verbeek et al, 1998), and is a sexually transmitted agent among these individuals (Martin et al, 1998). In Southeast Asia and the Caribbean, HHV-8 might be a relatively newly introduced pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…In these countries, horizontal transmission and mother-to-child transmission are likely to occur (Bourboulia et al, 1998;Luppi et al, 1998;Gessain et al, 1999). In countries with a low incidence of classic or endemic KS, HHV-8 is predominantly found in homosexual men at risk of developing KS Martin et al, 1998;Verbeek et al, 1998), and is a sexually transmitted agent among these individuals (Martin et al, 1998). In Southeast Asia and the Caribbean, HHV-8 might be a relatively newly introduced pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 The presence of LANA antibodies in HIV-positive patients strongly correlates with the risk of developing Kaposi sarcoma. 4 Monoclonal antibodies to LANA have recently been developed for use in formalin-fixed and frozen tissues, and have been shown to be reliable markers of latent HHV-8 infection in Kaposi sarcoma as well as other HHV-8-associated processes, such as primary effusion lymphoma and multicentric Castleman disease. 5,6 A small number of studies have shown LANA expression to be specific for Kaposi sarcoma among vascular tumors occurring in the general population.…”
mentioning
confidence: 99%
“…In MSM who are HIV negative and asymptomatic, infection rates have ranged from 16.8 to 22.1% (1,3,13). An epidemiological relationship between male homosexual activities and HHV-8 infection has been demonstrated in studies undertaken in different countries (1)(2)(3)8,9,13).…”
mentioning
confidence: 99%